Evaluating the Level of Arbitration Culture for Handball Coaches in Iraq - Haroon, Mokhlad Neamah; Dahash, Adel Mohammed; Algburi, Ayman Hani Abed (International Journal of Psychosocial Rehabilitation, 2020)
Abstract–The research objectives to: • Setting levels for the arbitration culture scale and applying it to handball coaches in • Knowing the level of arbitration culture for handball coaches in • Evaluating the level of arbitration culture for handball coaches in The researchers used the descriptive approach with the survey method to determine the level of arbitration culture, and the scale was applied in its final form to a sample consisting of handball coaches in Iraq for the sports season 2019-2020, and after that the researchers set levels of the arbitration culture scale and applied it to handball coaches in Iraq, and used Researchers Statistical Bag for Social Sciences (SPSS) Seventeenth Edition. The most important of the following conclusions were reached: • Five levels of arbitration culture scale were • The ability of the arbitration culture scale that researchers applied in measuring the arbitration • The majority of handball coaches in Iraq enjoy an average level in the arbitration culture